2008
DOI: 10.1001/archopht.126.8.1076
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Apolipoprotein A-I and Apolipoprotein H Levels in the Vitreous Fluid and Overexpression in the Retina of Diabetic Patients

Abstract: Objectives: To determine levels of apolipoprotein (apo) A-I and apo H in the vitreous fluid of patients with proliferative diabetic retinopathy (PDR) and to examine whether apo A-I and apo H messenger RNA (mRNA) levels are overexpressed in the diabetic retina. Methods: Vitreous samples from 4 diabetic patients with PDR and 8 nondiabetic patients with macular hole were selected for proteomic analysis. Fourteen additional samples (7 from patients with PDR and 7 from patients with macular hole) were used for West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 38 publications
2
56
0
1
Order By: Relevance
“…Simo et al studied vitreous samples from 4 diabetic patients with PDR and 8 nondiabetic patients with macular hole for proteomic analysis of ApoA1 and ApoH [54]. The authors found that intravitreous ApoA1 and ApoH levels were significantly higher in patients with PDR than in the control group.…”
Section: Associations With Nontraditional Lipid Markersmentioning
confidence: 99%
“…Simo et al studied vitreous samples from 4 diabetic patients with PDR and 8 nondiabetic patients with macular hole for proteomic analysis of ApoA1 and ApoH [54]. The authors found that intravitreous ApoA1 and ApoH levels were significantly higher in patients with PDR than in the control group.…”
Section: Associations With Nontraditional Lipid Markersmentioning
confidence: 99%
“…29 Apo A 1 is a potent scavenger of oxygen-reactive species, and may have a role in protecting retina from the oxidative stress due to diabetes. 30 Garcia-Ramirez et al identified several components of the complement factor (C4b, factor B, C3 and C9) in PDR vitreous. 31 These authors postulated that activation of the complement cascade leads to initiation and progression of thrombosis, leucostasis and apoptosis, causing the vascular lesions in diabetic retinopathy.…”
Section: The Vitreous Proteome In Diabetic Retinopathymentioning
confidence: 99%
“…The levels of PEDF, a potent inhibitor of angiogenesis, have not been found to be consistent across different studies, some reporting it to be down-regulated 31 ; and others as up-regulated 27,29 in the PDR vitreous. Other proteins that have been found to be increased in abundance in the diabetic vitreous include apo H 30 , prostaglandin –D2 synthetase, plasma glutathione peroxidase, intra retinol binding protein, catalase, 32 enolase, 32 prostaglandin-H2 D isomerase, 33 serine protease inhibitor, 33 ankyrin repeat domain 15 protein, 33 angiotensiogen 27 , prothrombin 27 , antithrombin III 27 , Factor XII 27 and peroxiredoxin-1. 27 …”
Section: The Vitreous Proteome In Diabetic Retinopathymentioning
confidence: 99%
“…However, Apo A-I was recently found in the vitreous fluid and human RPE cells. 23 Apo A-I has a protective effect on the corneal epithelium and may improve the epithelial conditions of the ocular surface. 24 Clusterin is also present in human tears.…”
mentioning
confidence: 99%